Hotel Tax Effectiveness Analysis and Taxes Advertising and Its Contribution to Increasing Regional Original Income (PAD) - Saranani, Inka Trydayanti; Asraf; Hasnita, Nita (SAN Scientific, 2023)
The purpose of this study was to determine the effectiveness and contribution of hotel taxes and advertisement taxes in increasing Kendari City's own-source revenue (PAD). This research uses a quantitative descriptive approach. The data sources in this study use primary data through unstructured interviews and secondary data obtained through documents or written data at the Kendari City Regional Revenue Agency, namely data on PAD revenue realization and hotel taxes and advertisement tax for the Kendari City Government for 2018-2021 and target amount data. and realization of Kendari City Hotel and Advertising Tax for 2018-2021. The data collection methods used in this research are Field Research, Archival Research and Library Research. The results of this study are that the effectiveness of Kendari City hotel taxes is categorized as very effective with an average percentage of 106.11% and the contribution of Kendari City hotel tax revenues in increasing PAD is categorized as highly contributing with an average percentage of 5.15%. The effectiveness of advertising tax in Kendari City is categorized as very effective with an average percentage of 106.81% and the contribution of Kendari City advertisement tax revenue is categorized as having less contribution with an average percentage of 1.20%.